Safe Haven Currencies - Žáková, Bianka (2024)
Although various studies with the pivotal point on safe haven currencies have been conducted throughout the last few decades, the attention of academics has been paid to diverse attributes of safe haven currencies. Thus, there has been no systematic research focusing on how turbulent times such are the spread of the highly infectious virus known as Covid-19 and the escalated armed conflict between Russia and Ukraine influenced the traditional safe haven currencies and how their roles differentiated during these geopolitical events. Therefore, this master`s thesis addresses a phenomenon known as safe haven currencies amid these enumerated geopolitical crises. Under the expression of safe haven currencies, it is comprehended hard currencies such as the Swiss franc, euro, American dollar, and Japanese yen. In this master’s thesis, we scrutinise whether, during these two global unprecedented occurrences, the adduced national tenders exhibited characteristics of safe haven assets. To analyse their behaviours, we first examine and compare macroeconomic figures among the currencies under review. Secondly, we analyse and discuss the relevance of the energy shock on the currencies, especially as a consequence of imposed sanctions against the Russian Federation. Subsequently, we utilise quantitative analytical methods, comprising descriptive and inferential statistics, to identify which of the observed national tenders demonstrated the behaviour of a safe haven asset. Lastly, we employ a qualitative approach in the form of a semi-structured interview with an expert from the finance sector who contributed meaningfully to the comprehension of various aspects linked to safe haven currencies.